From invisible to tangible power in rural late antique Lusitania: between text and material evidence - Carneiro, André (2021)
This paper analyses settlement and land evolution in the territory of Augusta Emerita (Mérida), the capital of the late Roman province of Lusitania, seeking to contrast the archaeological data related to the new occupation profiles of the sites and evidence for villa life and changes in ownership, with the perception conveyed by the Vitas Sanctorum Patrum Emeritensium on this specific phenomenon of rural change. The resulting image will contribute to enhancing current understanding of the local context and its dynamics in Lusitania after the collapse of the Empire.